Analisis Pengaruh Paket Remunerasi dan Stres Kerja terhadap Turnover Intention dengan Kepuasan Kerja sebagai Variabel Mediasi pada Karyawan - I Nyoman Tri Sutagana; Rihfenti Ernayani; Festus Evly R.I. Liow; Cut Susan Octiva; Rianti Setyawasih (BUDGETING : Journal of Business, Management and Accounting, 2022)
This study explains the effect of work stress and remuneration packages on turnover intention, using job satisfaction as a mediator. The object of research is one of the companies engaged in the palm oil sector in Jakarta, PT Kruing Lestari Jaya. This study discusses the theory of the four research variables, namely work stress, remuneration packages, turnover intention, and job satisfaction. This study used quantitative methods through the distribution of questionnaires via Google Form to 48 respondents, which were then processed using the SPSS version 25.0 program using saturated sampling techniques for sampling data. The results showed that work stress has a significant effect on turnover intentions. Remuneration packages have a significant effect on turnover intention. Job satisfaction does not mediate work stress and turnover intention. Job satisfaction does not act as a buffer between the remuneration package and the turnover intention. From the results of the study, it can be concluded that direct influence has a greater value than indirect influence. The job satisfaction does not mediate the effect of the remuneration package on turnover intention at PT Kruing Lestari Jaya. Keywords : Job Satisfaction, Remuneration Package, Work Stress and Turnover Intention